MicroRNAs: master regulators in host–parasitic protist interactions. Issue 6 (15th June 2022) - Rojas-Pirela, Maura; Andrade-Alviárez, Diego; Medina, Lisvaneth; Castillo, Christian; Liempi, Ana; Guerrero-Muñoz, Jesús; Ortega, Yessica; Maya, Juan Diego; Rojas, Verónica; Quiñones, Wilfredo; Michels, Paul A.; Kemmerling, Ulrike
Abstract : Abstract : MicroRNAs (miRNAs) are a group of small non-coding RNAs present in a wide diversity of organisms. MiRNAs regulate gene expression at a post-transcriptional level through their interaction with the 3′ untranslated regions of target mRNAs, inducing translational inhibition or mRNA destabilization and degradation. Thus, miRNAs regulate key biological processes, such as cell death, signal transduction, development, cellular proliferation and differentiation. The dysregulation of miRNAs biogenesis and function is related to the pathogenesis of diseases, including parasite infection. Moreover, during host–parasite interactions, parasites and host miRNAs determine the probability of infection and progression of the disease. The present review is focused on the possible role of miRNAs in the pathogenesis of diseases of clinical interest caused by parasitic protists. In addition, the potential role of miRNAs as targets for the design of drugs and diagnostic and prognostic markers of parasitic diseases is also discussed.